Criteria used by South African companies to enter emerging markets - Naidoo, Vebashini (My University, 2014)
Emerging markets and Africa in particular, seem to be the last untapped frontier for many businesses looking to expand beyond their borders. For South African companies the African continent is their backyard, and even though every country in Africa is unique and offers many challenges, they offer a great deal of opportunity and are a comfortable fit for most South African companies. The study set out to discover the factors considered by South African companies when making investments in other emerging markets. Furthermore, it explored whether the strategy, and products and service set differed for each emerging market. Fourteen in-depth interviews, using open-ended questions, were conducted with large South African firms, most of which are concentrating on expansion into Africa. The number of factors that could be considered is wide and varied and has been the focus of many studies. However, the information regarding the specific factors used by South African firms is lacking. The study revealed that some factors were more important than others were. Political stability, repatriation of funds, partners, economic stability, size of market, competitor environment and infrastructure were the most important criteria considered in the location decision. There was overlap on most of these important criteria among the firms. Surprisingly, factors that were not mentioned in the literature reviewed were that of local partners and competitors in the host country. A local partner in the host country is considered vital to an expansion. The competitors in the proposed market, if they are vast or have a large market share, can deter firms from that location. The research further showed that the strategy for each emerging market is different from that of the home market and from other emerging markets. Each African country is unique and requires a unique strategy. In more than 50 percent of the firms interviewed, the products and services sold in each country is tailored for local tastes, this correlated with the company strategy as many would like to be seen as a local company within the host country.
Keywords: International business enterprises -- Africa.